محطات الطاقة الشمسية في الجزائر الواقع الحالي والآفاق المستقبلية - جابري، عبد القادر; كينة ،عبد الحفيظ (University of Eloued جامعة الوادي, 2025)
تعد الطاقة الشمسية أحد أهم البدائل الاستراتيجية لتحقيق التحول الطاقوي في الجزائر، لما تتمتع به البلاد من موارد شمسية هائلة تمتد على معظم أراضيها. يهدف هذا المقال إلى دراسة واقع محطات الطاقة الشمسية في الجزائر، من خلال تحليل المشاريع المنجزة ضمن البرنامج الوطني للطاقات المتجددة، وتحديد أهم التحديات التقنية والمالية التي تعيق تطورها، كما يتناول المقال دراسة حالة لإحدى المحطات الشمسية النموذجية لتقييم مردوديتها وآفاق تطويرها، وتخلص الدراسة إلى أن الجزائر تمتلك إمكانات كبيرة لتوسيع إنتاج الكهرباء من الطاقة الشمسية، شريطة تفعيل آليات التمويل، وتطوير الإطار القانوني، وتعزيز الشراكة بين القطاعين العام والخاص. Solar energy is one of the key strategic alternatives for achieving Algeria’s energy transition, given the country’s vast solar resources across most of its territory. This paper examines the current status of solar power plants in Algeria by analyzing completed projects under the National Renewable Energy Program and identifying the main technical and financial challenges. It also presents a case study of a representative solar plant to assess its performance and development prospects. The study concludes that Algeria has significant potential to expand solar electricity generation, provided that financing mechanisms are strengthened, the legal framework is updated, and public–private partnerships are promoted
Solar Power Plants in Algeria: Current Situation and Future Prospects
مقال
Keywords: الطاقة الشمسية; الجزائر; المحطات الشمسية; الأمن الطاقوي; محطة الطاقة الشمسية بغرداية.; Solar energy; Algeria; solar power plants; energy security; Ghardaïa Solar Power Plant